PP-031 Nystatin-lidocaine sugar free pastilles: A stability and characterisation study. (14th February 2016) - Silva, AF Cosme; Marto, J; Salgado, A; Silva, A; Rodrigues, V; Ferreira, MP; Almeida, AJ
Abstract : Background: Patients with oral mucositis often present painful ulcerative lesions that hamper the administration of drugs. The development of dosage forms that promote the comfort of the patient may be an alternative to the currently available solutions. The initial formulation of nystatin pastilles and lidocaine 1 was flavoured with sucrose, an excipient not recommended for patients with an increased risk of oral infections. In accordance, it is important to develop a new sugar-free formulation as well as to study its palatability and texture behaviour during its dissolution. Purpose: Development, characterisation and stability study of a new formulation of nystatin and lidocaine sugar-free pastilles. Material and methods: The nystatin and lidocaine pastilles were formulated from raw material without sucrose in its constitution. Studies included optimisation of the physicochemical properties of the pastilles (evaluation of their behaviour by texturometry after partial dissolution in artificial saliva, assessing the compatibility between active excipients and substances, and antifungal activity against Candida albicans ATCC 10231). 2 Physicochemical and microbiological stability was assessed for a period of 60 days. After informed written consent, 35 volunteers rated the palatability, aspect and flavour of the pastilles by answering a questionnaire. Results: The texture profile analysis after dissolution showed a decrease in hardness, gumminess and chewiness of the pastilles and an increase in mucoadhesion. No chemical interactions were detected between active substances and excipients, and the formulation proved to be effective in inhibiting the growth of C albicans . The stability test supports a period of use of 60 days at 5 ± 3°C and protected from light. The questionnaire results showed that 76% would take the pastille if prescribed. Conclusion: The newly developed formulation had suitable characteristics for oral administration. The behaviour of the pastilles after partial dissolution in saliva is clearly advantageous in terms of its smooth texture which facilitates use by the patient with oral mucositis, contributing to comfort and improving therapeutic adherence. Furthermore, the increased mucoadhesion property makes it the most effective topical action in relation to the often used mouthwash. References and/or Acknowledgements: Lozenges: Innovation in the treatment of oral mucositis. EAHP poster. Hamburg, 2015 European Pharmacopoeia 8.6. 2014, 8th edn No conflict of interest.